The competencies of principals in ensuring sustainable education: Teachers' views - Fatma Köybaşı Şemin (Institute of Advanced Engineering and Science, 2019)
This study aimed to reveal the opinions of teachers about the competencies of school administrators in order to ensure the sustainability of education in schools. It was a pneumology study designed with qualitative research method. The study group consists of fifteen teachers from schools located in five different educational zones across the center of Sivas, a city in Central Turkey. Study data were analyzed with content analysis to determine the factors that provide educational sustainability in schools. According to the results; solidarity and structured work characteristics among school administrators to fulfill the objectives of the school affect the adequacy of education in a positive way; while institutionalism and limiting of the capacity have an opposite effect. In relation to capacity building for taking the school culture to future, school administrators have a high opinion of opening up to the neighborhood besides school culture supply and demand. Lastly, for carrying the school into the future, teachers expect school leaders to exhibit behaviors with emphasis on specific themes as ethics, motivation, and awareness.